Plasmablastic lymphoma in HIV positive patients in the Free State Province of South Africa - Jordaan, Jacoline (University of the Free State, 2017)
2.1 Methods: The patient sample of this study consisted of all HIV-positive patients that were diagnosed with PBL in the period between 2005 and 2013 in the Free State Province of South Africa and who were treated by the Department of Oncology at the Universitas Hospital Complex. The study design is a retrospective study with descriptive and analytical components aimed at analysing the patient profile and the performance of a range of treatment regimes. 2.2 Results: Fifty nine patients from one institution were evaluated after all exclusions. The mean age at diagnosis with PBL was 39,1 years with the gender distribution favouring males. Forty one point eight percent of patients presented with a performance status of ECOG 1. The amount of patients diagnosed with HIV prior the diagnosis of PBL was 59,3%. A third of patients were on HAART prior to diagnosis of PBL and 37% of patients were documented to be started on HAART with diagnosis of PBL. The median CD4 value on diagnosis of PBL was 108,5. The most popular extra nodal site was the oral cavity. According to our statistics only 38 of our patients received some form of treatment for their PBL, 21 patients were either too critical or lost to follow up to start treatment. Thirty seven patients received chemotherapy. Radiation therapy was part of the treatment for 12 of the patients. The median follow up time was 2,3 months. Progression free survival at 3 months for our study population was 90,8% (95%CI 83,1%-98,5%). The overall survival of patients according to treatment modality at 3 months calculated as follows: HAART prior to PBL (n=14) 71,43%, HAART with PBL (n=12) 91,66%, No HAART (n=9) 55,56%, patients receiving chemotherapy as treatment modality (n=27) 92,59%. 2.3 Conclusions: The importance of improved management of HIV is highlighted by the results of the study. If better control over HIV and a patient’s general immunity can be achieved, more intensive chemotherapy regimes can be employed. Therefore, HAART is the mainstay and most important factor of the treatment of PBL. By starting HIV positive patients on HAART at an earlier stage in the disease (despite the CD4 value) might help in the survival of PBL patients or play a role in preventing PBL.
Keywords: Lymphomas; AIDS (Disease) -- Patients -- South Africa -- Free State; HIV-positive persons -- South Africa -- Free State; Dissertation (M.Med. (Radiation Oncology))--University of the Free State, 2017